2006
DOI: 10.1182/blood.v108.11.1757.1757
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor-Bearing Microparticles Derived from Tumor Cells: Impact on Coagulation Activation.

Abstract: Thromboembolic disease is a frequent complication in cancer. Tissue factor (TF), shown to be involved in tumor growth and metastasis, is also considered to play a central role in the pathogenesis of cancer-associated thrombosis. Circulating TF-bearing microparticles (TF+ MPs) have been found in the plasma of patients with different malignancies and are thought to contribute to their hypercoagulable state. Although numerous studies have focused on TF+ MPs derived from blood cells, there is no information availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(97 citation statements)
references
References 0 publications
7
88
2
Order By: Relevance
“…24 Studies in animal models show that the intravenous injection into mice of MP derived from human tumor cells and expressing high levels of TF, induces a TF-dependent activation of coagulation, which results in a DIC-like syndrome. 25 TF-positive MPs have been reported elevated in patients with solid tumors and VTE, being gastric and pancreatic cancers the most studied. 21,23,26 Among hematologic malignancies, high levels of blast cells-derived MPs have been found in patients with APL 27 and other acute myeloid leukemias, 28 and in patients with multiple myeloma.…”
Section: Clotting Activation By Cancer Cell-associated Mechanisms Canmentioning
confidence: 99%
“…24 Studies in animal models show that the intravenous injection into mice of MP derived from human tumor cells and expressing high levels of TF, induces a TF-dependent activation of coagulation, which results in a DIC-like syndrome. 25 TF-positive MPs have been reported elevated in patients with solid tumors and VTE, being gastric and pancreatic cancers the most studied. 21,23,26 Among hematologic malignancies, high levels of blast cells-derived MPs have been found in patients with APL 27 and other acute myeloid leukemias, 28 and in patients with multiple myeloma.…”
Section: Clotting Activation By Cancer Cell-associated Mechanisms Canmentioning
confidence: 99%
“…Patients with malignancy experience a hypercoagulable condition (1,2). There are multiple risk factors for thrombosis and patients with malignancy face a four-to seven-fold increased risk of venous thromboembolism (VTE) compared to patients without malignancy (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies identified D-dimer reflects the activation of the blood coagulation system, and high D-dimer levels were also associated with a poor response to the anticancer treatment (17). Studies have shown that malignant cells aberrantly express tissue factor and may be involved in the induction of cancer-associated thrombosis (13,18).…”
Section: Discussionmentioning
confidence: 99%